2009
DOI: 10.1136/adc.2007.115915
|View full text |Cite
|
Sign up to set email alerts
|

Teenage pregnancy: who suffers?

Abstract: In this review, we examine the epidemiology of teenage pregnancy (girls aged 15-17 years) in the UK and consider the evidence for its impact on the health and well-being of the mother, the baby, the father and society. There has been some decrease in the teenage pregnancy rate over the last decade in the UK but rates are still considerably higher than those in other European countries. Pregnancy and childbirth during the teenage years are associated with increased risk of poorer health and well-being for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
131
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 45 publications
(58 reference statements)
13
131
1
9
Order By: Relevance
“…Teenage women were at increased risk of complications such as PROM but this complication did not differ significantly between the groups, similar findings reported by other investigators [4]. Premature rupture of membranes has been attributed to biological immaturity of the uterus as well as the shortness of the cervix, which leads to increase the risk of ascending infections and PROM, which may be due to poor hygiene in this group of women [9].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Teenage women were at increased risk of complications such as PROM but this complication did not differ significantly between the groups, similar findings reported by other investigators [4]. Premature rupture of membranes has been attributed to biological immaturity of the uterus as well as the shortness of the cervix, which leads to increase the risk of ascending infections and PROM, which may be due to poor hygiene in this group of women [9].…”
Section: Discussionsupporting
confidence: 77%
“…Majority of early and late teenage women in this study delivered vaginally (85.0 vs. 82.9 %). These findings are supported by others, this may be due to the presence of more functional myometrium, greater connective tissue elasticity, and lower cervical compliance that allowed for more spontaneous vaginal deliveries in young age group [4,7]. Five minutes Apgar score, which is more relevant in assessing newborn health was similar in the two groups, 5 min Apgar score considered as a predictor for postneonatal hospitalization, a Canadian study showed that with decreasing of 5 min Apgar score, the risk of hospitalization in the first 10 years of life is increased [10].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Second, teenage pregnancy is associated with poorer maternal health outcomes. The same review [4] described higher risks of obstetric complications such as hypertension, pre-eclampsia, urinary tract infection and anaemia. The increased risk of negative health outcomes for teenage mothers continues into adulthood and old-age with an increased risk of cardiovascular disease [5] and more generally, poorer physical health compared to other women [6].…”
mentioning
confidence: 99%
“…First, teenage pregnancy is also associated with poorer health behaviours. A review [4] examined health behaviours during the pregnancies of teenagers in UK and found that increased use of tobacco and alcohol and poorer nutrition were more common in these mothers than others. Second, teenage pregnancy is associated with poorer maternal health outcomes.…”
mentioning
confidence: 99%